Incentivo perverso das reservas internacionais: O caso das empresas exportadoras brasileiras - Werther Vervloet; Márcio Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2009)
– Starting with Lehman Brother's demise in September 2008, the Brazilian real fell 42% vis-à-vis the US dollar. Such large exchange rate depreciation would typically cheer exporters up. However, it was later found that many export firms, including multibillion dollar ones, had suffered large financial losses. These capital losses came not from garden variety currency mismatches, but from complex derivative products. We analyze the problems created by this misuse of derivatives by export companies in Brazil in 2008. Besides a careful description of the most relevant cases and of the derivative that caused the problems, we also present evidence that the derivative was not used as a hedge, but as a speculative instrument. The Brazilian case—just one among many where export firms in emerging markets sold USD short much beyond the point necessary to hedge their USD revenues—shows that the benefits of international reserves accumulation by the government may be jeopardized by perverse incentives generated to the private sector. We discuss and recommend a few prudential regulation measures.
Keywords: 330; International Reserves; Derivatives; Financial Hedge; Export Firms. JEL Codes: F41; G01; G15; G32; 34; G38.